How Social Media Marketing Management Builds Brand Loyalty through Customer Engagement: Evidence from the F&B Industry in Indonesia - Novi Angga Safitri; Muhammad Riza Hafizi (Yayasan Sinergi Kawula Muda, 2026)
Introduction: This study examines how social media marketing contributes to brand loyalty in Indonesia’s food and beverage (F&B) industry by explicitly testing customer engagement as the mediating mechanism, addressing prior debate on whether social media influences loyalty directly or primarily through engagement while highlighting the study’s novelty in demonstrating a partial mediation model in which the indirect pathway is slightly stronger than the direct effect. Methods: A quantitative survey was conducted with 400 millennial and Generation Z consumers selected using purposive (criterion-based) sampling from online communities of F&B brand followers on Instagram, TikTok, and Facebook. Data were collected through a structured Likert-scale questionnaire and analysed using SEM-PLS with bootstrapping procedures. Results: The findings indicate that social media significantly affects customer engagement (β = 0.68; p < 0.001) and brand loyalty directly (β = 0.40; p < 0.01). In addition, social media influences brand loyalty indirectly through customer engagement (β = 0.401; p < 0.01), confirming a partial mediation model in which customer engagement serves as a mediator and the indirect pathway is slightly stronger than the direct pathway. Conclusion: Brand loyalty in the F&B industry is not generated merely through social media presence but through the effective management of consumers’ cognitive, emotional, and behavioural engagement. Social media functions as a strategic managerial tool when it is leveraged to foster meaningful and interactive engagement, which represents the more dominant pathway in strengthening loyalty.